Application of wood ash on acidic soil at landfill area / Wan Noni Afida Ab Manan and Fatihah Abdullah - Ab Manan, Wan Noni Afida; Abdullah, Fatihah (Universiti Teknologi MARA Cawangan Pahang, 2020)
Utilisation of wood ash might improve soil pH especially in landfill area. This study aims to discover the potential of wood ash in decreasing acidity (increase pH) in soil especially at landfill area which is known as disposal site for household waste. Two types of sawdust which are Acacia mangium willd sp. and Endospermum malaccense sp. were collected and wood ash was produced by pyrolysis process at 600°C for 3 hours. Fourier-transform infrared (FTIR) analysis was then used to determine the chemical composition of wood ash. The landfill soil's plot selected for the experiment was located in Felda Jengka 10 with an area of 100 m2. Wood ash amount equivalent to 0.1, 0.25, 0.5, and 1 kg/m2 were used as the pilot test. The usage of wood ash was proven to be effective in increasing the pH (reduce acidity) of the landfill soil. The highest increment of soil pH; up to pH 8.90, was achieved when 1 kg/m2 of wood ash (Acacia mangium willd sp.) was added. This result suggests that utilisation of wood ash on acidic soil will benefit to both soil pH and environment thus possibly can be used as an alternative to the practice of lime at a more reasonable price.